Determining the Coefficient of Restitution for Imperfect Elastic Collisions between Glass Marbles and Ceramic Surfaces - Mahendra Kusuma Nugraha; Ernawatil Gani; Jumriadi (Jurnal MIPA, 2024)
Time-lapse videography was employed to observe the dynamics of imperfect elastic free-fall collisions between a standard glass marble and a ceramic-tiled floor surface, using a SHARP® Aquos Sense 4+ smartphone camera with a shutter speed of 30 frames per second (fps). The events were recorded and analysed using the frame-splitting method, which was then visually observed to determine the height of each bounce. The analysis revealed that the average coefficients of restitution for the collisions were  and , with the initial free-fall heights being 20.3 cm and 16.2 cm respectively for the first and second trials. These experiments illustrate that every event signifies an imperfect elastic collision, showing how mechanical energy dissipates from the marble into its surroundings since ε is not equal to 1. The slight variations in the coefficient outcomes occur due to the constraints imposed by the laws of thermodynamics. Untuk menyelami potensi lanjut dari videografi jeda-waktu, metode ini digunakan untuk mengamati dinamika tumbukan jatuh bebas elastis tak sempurna antara kelereng kaca dan lantai keramik, menggunakan kamera ponsel SHARP® Aquos Sense 4+ dengan kecepatan rana 30 kerangka per detik. Peristiwa-peristiwa tersebut direkam dan dianalisis menggunakan metode pemisahan kerangka, yang kemudian diamati secara visual untuk menentukan tinggi setiap pantulan. Analisis mengungkapkan bahwa koefisien restitusi rata-rata untuk tabrakan tersebut adalah  dan , dengan tinggi jatuh bebas awal masing-masing adalah 20.3 cm dan 16.2 cm untuk percobaan pertama dan kedua. Eksperimen-eksperimen ini menggambarkan bahwa setiap peristiwa menunjukkan sebuah tumbukan elastis yang tidak sempurna, menunjukkan bagaimana energi mekanik tersebar dari kelerang ke sekitarnya karena ε tidak sama dengan 1. Variasi kecil dalam hasil koefisien terjadi karena batasan yang diberlakukan oleh hukum termodinamika.